Emission Reduction Effect and Mechanism of Auto-Purchase Tax Preference - Kai Lisa Lo; Yaqi Fan; Congzhi Zhang; Jackson Jinhong Mi (Journal of Advanced Transportation)
As a modern means of transportation, the automobile plays an important role in people’s travel. However, the environmental and energy problems brought by the automobile industry cannot be ignored. Based on unique Chinese urban and new car registration data, this paper empirically analyzes the emission reduction effect of car purchase tax incentives, its spatial heterogeneity, and impact on car consumption structure using difference-in-difference model, regression discontinuity design model, and other methods. We find that the tax incentives can effectively suppress the emission of urban pollutants. The quantile regression shows that the emission reduction effect of the tax incentives shows a dynamic change characteristic of weakening as the pollution level in cities increases. In addition, tax incentives for the purchase of low-energy consumption vehicles increase the market share of small-emission vehicles and change the consumption structure.